2018
DOI: 10.1038/s41598-018-26950-z
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate mediated metabolic neutralization mitigates propionate toxicity in intracellular Mycobacterium tuberculosis

Abstract: Metabolic networks in biological systems are interconnected, such that malfunctioning parts can be corrected by other parts within the network, a process termed adaptive metabolism. Unlike Bacillus Calmette-Guérin (BCG), Mycobacterium tuberculosis (Mtb) better manages its intracellular lifestyle by executing adaptive metabolism. Here, we used metabolomics and identified glutamate synthase (GltB/D) that converts glutamine to glutamate (Q → E) as a metabolic effort used to neutralize cytoplasmic pH that is acidi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
22
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 73 publications
(87 reference statements)
8
22
1
3
Order By: Relevance
“…Bacteria use ammonium (NH4 + ), which is first incorporated into Glu and Gln and works as a primary nitrogen donor, as the key molecule for central nitrogen metabolism 27 . Lee et al found that Mtb converts Gln to Glu using glutamate synthase to neutralize cytoplasmic pH in the host environment, which makes it a successful intracellular pathogen 28 . Maintenance of the Glu pool is also linked to ergothioneine, which plays a critical role in the redox homeostasis of Mtb 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Bacteria use ammonium (NH4 + ), which is first incorporated into Glu and Gln and works as a primary nitrogen donor, as the key molecule for central nitrogen metabolism 27 . Lee et al found that Mtb converts Gln to Glu using glutamate synthase to neutralize cytoplasmic pH in the host environment, which makes it a successful intracellular pathogen 28 . Maintenance of the Glu pool is also linked to ergothioneine, which plays a critical role in the redox homeostasis of Mtb 29 .…”
Section: Discussionmentioning
confidence: 99%
“…While the phagosomal proteome has been widely investigated, other phagosomal 'omics' such as the lipidome and glycome have been studied to a significantly lesser extent [57,58]. Because of the increasingly recognized contribution of lipids, carbohydrates and metabolites to phagosomal dynamics, defining changes in their molecular landscapes in phagosomes, will likely render important advances in the field, especially in the understanding of host-pathogen interactions [59].…”
Section: Proteomicsmentioning
confidence: 99%
“…Also, accumulating evidence showed that dysregulated ETC activities and ATP depletion are two molecular signals that enhance bacterial persister formation 20–23 . Thus, we hypothesize that Mtb persisters monitor the metabolic vulnerability induced by ETC dysregulation and ATP depletion following antibiotic treatment, and respond by modifying the perturbed metabolic networks to gain drug tolerance 24 .…”
Section: Introductionmentioning
confidence: 99%